2021
DOI: 10.1002/ecs2.3749
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of communities interacts with regional heterogeneity in driving species diversity: a mesocosm experiment

Abstract: According to metacommunity theory and previous experiments, inter-patch dispersal rates may alter species diversity at local to regional scales. In this study, we tested the predictions of metacommunity theory regarding the effect of dispersal rates on diversity, with a focus on the impact of environmental heterogeneity. Experiments were conducted in which the dispersal frequencies of freshwater nematode communities and the heterogeneity of local environmental conditions were factorial manipulated by maintaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Since many passive dispersers are lost with drying and it takes time for them to recolonise rewetted streams (Bogan & Boersma, 2012;Kappes & Haase, 2012), more perennial sites tend to diverge in their composition as greater species number promotes niche partitioning between habitat patches. In the case of active dispersers, as the spatiotemporal connection between sites increases the communities become more homogeneous due to mass effects (Gansfort et al, 2021;Heino et al, 2015;Sarremejane et al, 2017). Overall, although the study sites were close to each other (mean distance between sites within a stream was around 1 km and all the streams were located within an approximate range of 100 km 2 ), the macroinvertebrate communities showed significant responses to spatiotemporal connectivity.…”
Section: Macroinvertebrate Communities Significantly Responded To Stconmentioning
confidence: 87%
See 1 more Smart Citation
“…Since many passive dispersers are lost with drying and it takes time for them to recolonise rewetted streams (Bogan & Boersma, 2012;Kappes & Haase, 2012), more perennial sites tend to diverge in their composition as greater species number promotes niche partitioning between habitat patches. In the case of active dispersers, as the spatiotemporal connection between sites increases the communities become more homogeneous due to mass effects (Gansfort et al, 2021;Heino et al, 2015;Sarremejane et al, 2017). Overall, although the study sites were close to each other (mean distance between sites within a stream was around 1 km and all the streams were located within an approximate range of 100 km 2 ), the macroinvertebrate communities showed significant responses to spatiotemporal connectivity.…”
Section: Macroinvertebrate Communities Significantly Responded To Stconmentioning
confidence: 87%
“…Since many passive dispersers are lost with drying and it takes time for them to recolonise rewetted streams (Bogan & Boersma, 2012; Kappes & Haase, 2012), more perennial sites tend to diverge in their composition as greater species number promotes niche partitioning between habitat patches. In the case of active dispersers, as the spatiotemporal connection between sites increases the communities become more homogeneous due to mass effects (Gansfort et al, 2021; Heino et al, 2015; Sarremejane et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting highlight of our study is the observed increase in beta diversity despite increase in dispersal, which is plausibly explained by the interactions of heterogeneity, connectivity and contingency. Although higher connectivity maintained by higher forest AI enhances dispersal and may lead to homogenisation under a depleted species pool, social heterogeneity at the metropolitan scale and landscape heterogeneity at the local scale can prevent homogenisation thus averting the decline of beta diversity (Gansfort et al, 2021;Suzuki & Economo, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the freshwater ecosystems, environmental heterogeneity is a key factor of nematode metacommunity as shown in a mesocosm experiment by Gansfort et al. (2021). The dispersal process is another important driver for the metacommunity of passive dispersal nematodes (Ptatscheck et al., 2020).…”
Section: Introductionmentioning
confidence: 99%